APOE-ε4 allele[s]-associated adverse events reported from placebo arm in clinical trials for Alzheimer's disease: implications for anti-amyloid beta therapy - Sato, Kenichiro; Niimi, Yoshiki; Ihara, Ryoko; Suzuki, Kazushi; Iwata, Atsushi; Iwatsubo, Takeshi (Frontiers in Dementia, 2024)
APOE-ε4 allele[s] is a risk factor for Alzheimer's disease (AD) and Amyloid-Related Imaging Abnormalities (ARIA) in anti-amyloid beta therapy, and is also associated with cerebrovascular risk factors such as hyperlipidemia or atherosclerosis. During AD clinical trials, APOE-ε4 carriers may experience neuropsychiatric adverse events (AEs) related to these risks, complicating the differentiation of ARIA from cerebrovascular events based on symptoms. This study aimed to examine the hypothetical impact of considering the APOE-ε4 allele's risk for non-ARIA AEs during AD clinical trials. We used data from the Critical Path for Alzheimer's Disease (CPAD) from the placebo arm of randomized controlled trials (RCT) for AD treatment. We determined whether AEs were reported more frequently in APOE-ε4 carriers, quantifying with reporting odds ratio (ROR) using a mixed effect model. We also evaluated the association between ROR levels and the prior probability that an AE is symptomatic ARIA. We analyzed 6,313 patients with AD or mild cognitive impairment in 28 trials. Of the prespecified 35 neuropsychiatric or related AEs, several had a significantly high ROR: "delusion" (ROR = 4.133), "confusional state" (ROR = 1.419), "muscle spasms" (ROR = 9.849), "irritability" (ROR = 12.62), "sleep disorder" (ROR = 2.944), or "convulsion" (ROR = 13.00). However, none remained significant after adjusting for Mini-Mental State Examination scores. There is no strong evidence to suggest that specific neuropsychiatric AEs occur more frequently without drug treatment association among APOE-ε4 carriers. The influence of APOE-ε4 allele[s] on the clinicians' assessment of the likelihood of ARIA during safety monitoring in anti-amyloid beta monoclonal antibody treatment might be unchanged, thus maintaining the current level of awareness of clinicians of AEs.